Rapid and sensitive electrochemical detection of oxidized form of glutathione in whole blood samples using Bi-metallic nanocomposites - Nagabooshanam, Shalini; Kumar, Akash; Ramamoorthy, Sharmiladevi; Saravanan, Nishakavya; Sundaramurthy, Anandhakumar (Chemosphere, 2024)
We report a facile one-pot synthesis of bimetallic nickel-gold (Ni–Au) nanocomposite for ultra-sensitive and selective electrochemical detection of oxidized glutathione (GSSG) by electrochemical deposition on fluorine doped tin oxide (FTO) substrate. The electrodeposition of Ni–Au nanocomposite on FTO was confirmed by various characterization techniques such as field emission scanning electron microscopy (FE-SEM), X-ray diffractometer (XRD) and Fourier transform infra-red (FTIR) spectroscopy. The cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) was utilized for the electrochemical characterization of glutathione reductase (GR)/Ni–Au/FTO working electrode at each stage of modification. The GR enzyme immobilized on the Ni–Au/FTO working electrode via glutaraldehyde cross-linking exhibited excellent selectivity against GSSG in the presence of nicotinamide adenine dinucleotide phosphate (NADPH). The immobilized GR enzyme breaks down the GSSG to reduced glutathione (GSH) and converting NADPH to NADP+ whereby generating an electron for the electrochemical sensing of GSSG. The synergistic behavior of bimetals and good electro-catalytic property of the fabricated sensor provided a broad linear detection range from 1 fM to 1 μM with a limit of detection (LOD) of 6.8 fM, limit of quantification (LOQ) of 20.41 fM and sensitivity of 0.024 mA/μM/cm2. The interference with other molecules such as dopamine, glycine, ascorbic acid, uric acid and glucose was found to be negligible due to the better selectivity of GR enzyme towards GSSG. The shelf-life and response time of the fabricated electrode was found to be 30 days and 32 s, respectively. The real sample analysis of GSSG in whole blood samples showed average recovery percentage from 95 to 101% which matched well with the standard calibration plot of the fabricated sensor with relative standard deviation (RSD) below 10%. Graphical abstract represented the detection of oxidized form of glutathione in blood sample using Au–Ni nanocomposite. [Display omitted] •A facile in-line transfer of Au–Ni nanocomposite on FTO surface is demonstrated.•The GR-immobilized enzymatic sensor exhibited excellent selectivity against GSSG.•Linear response with lower limits of detection of about 6.8 fM was achieved.•Improved selectivity and sensitivity caused by synergistic signal amplification of Au–Ni.•The developed sensor is tested in real blood samples by spiking known concentrations of GSSG.